2018
DOI: 10.1177/0892705718772872
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of morphology, crystallization and static and dynamic mechanical properties of long glass-fibre–reinforced polypropylene composites under thermo-oxidative ageing

Abstract: In this work, the static and dynamic mechanical properties, crystallization behaviours, and morphology of long glass-fibre–reinforced polypropylene (PP) composites with thermo-oxidative ageing time from 0 day to 50 days at 120°C were investigated and discussed. The static mechanical properties showed a global decrease in tensile, bending and impact strengths with increasing ageing time. From the results obtained by scanning electronic microscopic observations, interface debonding clearly occurred between the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the rubbery region, values of storage moduli increase with frequency increase in all the samples at 10 Hz frequencies. Similar reports have shown that storage modulus increases with frequency [32]. In this region, the increase in values of storage moduli due to an increase in frequencies follows the order: C4 > C3 > C6 > C5 > C2 > C1 > C7.…”
Section: Effect Of Frequency Variations On Storage Modulussupporting
confidence: 75%
See 1 more Smart Citation
“…In the rubbery region, values of storage moduli increase with frequency increase in all the samples at 10 Hz frequencies. Similar reports have shown that storage modulus increases with frequency [32]. In this region, the increase in values of storage moduli due to an increase in frequencies follows the order: C4 > C3 > C6 > C5 > C2 > C1 > C7.…”
Section: Effect Of Frequency Variations On Storage Modulussupporting
confidence: 75%
“…The highest peaks of loss moduli curves were shown for composite sample C4 at 10 Hz frequencies, followed by C3, C6, C5, C2, C1 and C7. These increases in loss moduli values could be due to an increase in molecular activities due to increased frequency [32].…”
Section: Effect Of Frequency Variations Of Loss Modulusmentioning
confidence: 99%
“…The above degradation was possibly attributed to the following reason. Under the catalysis of external light, heat and oxidation [ 62 , 63 ], C-H bonds in the polypropylene chain segment were easy to break and produced more active free radicals, which caused the continuous degradation reaction. For the present exposure, high temperature and oxygen in distilled water acted as the catalysts of the matrix for chemical reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Te composite's performance and mechanical properties are subject to the infuence of various factors, including the intrinsic properties of the individual components, the relative proportions of the constituent phases, the alignment of reinforcing fbers, and the extent of adhesion between the polymer matrix and the reinforcements. Consequently, a comprehensive body of research has been undertaken in recent years to elucidate the impact of these factors on the resulting mechanical properties of composites, with the aim of broadening their scope of utility [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Te introduction of elastomeric properties that enhance the mechanical performance of the composite is in great demand [13,14]. Fibers can also be added to increase the strength, stifness, and heat defection temperature of polypropylene composite [5][6][7][8][9]. Glass fbers are commonly used in fabricating composites as reinforcement [11].…”
Section: Introductionmentioning
confidence: 99%